Integration of the Electronic Chart Display and Information System (ECDIS) and Automatic Radar Plotting Aid (Arpa) to Enhance Object Detection, Identification, and Tracking - Amirullah Amirullah; Dwi Antoro; Henny Sutryani; Yohanna Nurika; Iman Ahmad (Jurnal Syntax Transformation, 2025)
Electronic Chart Display and Information System (ECDIS) and Automatic Radar Plotting Aid (ARPA) have become critical components in modern maritime navigation, contributing significantly to situational awareness, collision avoidance, and voyage planning. Despite their importance, the effectiveness of these navigational technologies depends largely on the competence of watchkeepers, the integration of system functions, and operational conditions on board. This study aims to analyze how the integration of ECDIS and ARPA enhances navigational awareness aboard KMP Jatra III, a Ro-Ro passenger vessel operating in Indonesian waters. Using a qualitative descriptive approach, data were collected through interviews, onboard observations, and documentation of navigational operations. The findings indicate that the integration of ECDIS and ARPA improves decision-making by providing real-time positional accuracy, automated radar target tracking, optimized route monitoring, and early detection of collision risks through Closest Point of Approach (CPA)/Time to CPA (TCPA). However, challenges such as screen saturation, overreliance on automation, environmental interference, and limited crew proficiency reduce the overall effectiveness of the integrated system. The study concludes that while ECDIS–ARPA integration significantly enhances navigational awareness, optimal outcomes can only be achieved through continuous training, strict adherence to STCW watchkeeping standards, and reinforcement of bridge resource management (BRM) principles.